Preliminary assessment of the chemical hazard potential of industrial plants in Kalookan City, Metro Manila - Cepeda, Marivie L.
There is a high concentration of industrial plants within densely populated areas in Kalookan City. The risks associated with the use of industrial chemicals may significantly increase the number of people endangered at any time by an accident involving these chemicals. There is a need to assess the hazard potential of these industries to help propose relevant measures on chemical safety and hazard control. A study was conducted to assess the hazard potential of 121 industrial plants located in Kalookan City to identify high risk or vulnerable areas. These plants were grouped into ten (10) industrial settings. The TIPS Ranking Method of preliminary assessment was developed to estimate the hazard potential of the industrial plants. The evaluation process involved the following steps: 1. Determination of attributes affecting the chemical hazard potential of industrial plants. 2. Assignment of relative weights to each attribute in terms of importance. 3. Description of levels, range characteristics and rating as to their effect on chemical hazard potential. 4. Estimation of the aggregate hazard potential of each type of industry. 5. Estimation of the cumulative hazard contribution of industries in a given source area.